Strategic Positioning of Emerging 5G Technology - Barriers and Perspectives - Ana Babić; Ernest Vlačić; Danijela Sokolić (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Since its introduction in the late seventies of the last century, mobile wireless communication has undergone significant stages of development, from analogue voice calls to nowadays latest state-of- the-art digital technology. The intense development of mobile communications networks, the increasing number of new types of mobile devices resulted in a large number of new applications being used and will increasingly be used in mobile connectivity and the expected growth of network traffic. The emerging and most promising one, the 5G technology, will probably not appear in the market until 2020 as a full scale commercial platform. 5G platform is expected to significantly improve customer service quality in the context of increased data volume in mobile networks and the growth of wireless devices with different services. In the near future, some of the main goals or requirements to be addressed by the 5G network are increased capacity, improved data transfer rates, reduced latency, and improved service quality. As per technological innovation theory taxonomy and strategic innovative positioning 5G technology is considered as game changer and disruptor. This paper displays how the global level key players, are preparing to introduce and boost the 5G network operability by using an inductive method, where broader EU arena with specific Croatian environment are used as a practitioners show cases.
Keywords: 650; disruptive innovation; mobile communication; strategic positioning; 5G technology